ANALISIS VISUAL DAN ISI KARYA KALIGRAFI DEKORASI HASIL MTQ KHATTIL QURAN TINGKAT KABUPATEN BULELENG KE-26 - Jajang Suryana; I Gusti Nyoman Widnyana; Elly Herliyani (Universitas Pendidikan Ganesha, 2018)
This descriptive qualitative research is aimed at analyzing the calligraphy participating inKhattil Quran Competition in the 26th MTQ in Buleleng Regency. The works were visually analyzedusing questioning approach which adapted Poster/visual analysis worksheet (Serianz, 2005) and TheNARA Photo Analysis Sheet, which contained 7 simplified main questions, comprising question about:1) dominant color, 2) use of symbols, 3) words that are presented visually; 4) the condition of the symbols( when they are needed); 5) message which are either explicitly stated or implied; 6) composition,dan 7) font variation. Content analysis was used to examine the style and composition of the calligraphy.The pattern of the calligraphy was analyzed by answering 6 questions that refer to letters variation,style of writing, accuracy of the contents (which was citation from the Quran), the rules of language usethat are applicable for the work of calligraphy.The results of the analysis indicate that most of the decorative calligraphy did not meet the criteriafor a competition. Seven out of nine decorative calligraphy (each of which representing the ninedistricts in the region) did not show the basic requirement as a calligraphy work of art. There werea number of writing style which neither visually representative nor accurate. Mistakes are consideredserious since the materials for creating the calligraphy were provided by the committee including theguidelines. Another mistake is the layout of the content (how to locate the verse, the choice of the fontstyle, and the reading direction) which was considered as the second type mistake which was to do withexperience with visual art management. This problem was to be followed up by the researcher team asa prospective area for community service program in the future.Key words: khattil quran, MTQ, calligraphy, analysis, mistakes, layout